Avaliação histomorfométrica de diferentes tipos de macrogeometria em implantes dentais: estudo em cães - Moraes , Guto Fidalgo Daumas (2014)
Objective: The aim of this study is to perform the histomorphometric analysis of four different macro-geometry of dental implants using animal model. Materials and Methods: For the present study seventy-two implants of different macro-geometry were tested in the left radius of eighteen beagle dogs (6 dogs per time in vivo, 4 implants per radius). The four different designs have one, two, three or four entry points in the apex geometry. The euthanasia was performed at one, three and six weeks and the implants were processed for histomorphometric analysis by means of bone-implant contact (BIC) and bone area fraction occupied (BAFO). For statistical analysis the GLM ANOVA was used. Results: For BAFO measurements a progressive increase (p ≤ 0,05) was observed for the implants with 2 entry-points to 1 (26.69 ± 3.88), 2 (42.72 ± 4.19) and 6 (53.92 ± 4,6) weeks and progressive increase was observed for the implantes with 3 entry-points 1 (22.25 ± 3.88), 3 (38.86 ± 4.19) and 6 (49.24 ± 4.6) weeks compared to implants of a one and four entry-points 1 (26.52 ± 4.16 / 23.69 ± 3.88), 3 (41.36 ± 5.05 / 38.23 ± 4.19) and 6 (48.48 ± 4.6 / 45,88 ± 4,6) weeks respectively. Conclusion: The results of the present study showed biocompatibility of all design evaluated and the better histomophometric resuls for 2 and 3 entry-points in the 1, 3 and 6 weeks.